PENGARUH SUBSTITUSI UBI JALAR KUNING, ISOLAT PROTEIN KEDELAI, DAN TEPUNG DAUN KELOR TERHADAP KANDUNGAN GIZI SERTA DAYA TERIMA MI INSTAN [Effect of Yellow Sweet Potato, Isolated Soy Protein and Moringa Leaves Powder Subtitution on Nutritional Value and Acceptability of Instant Noodle] - Ranty Restiartanti Agus; Rita Ismawati (Universitas Airlangga, 2018)
Instant noodle is an alternative source of energy based on wheat fl our. The consumption of instant noodle in Indonesia is quite high. Instant noodle innovation with local food substitution is a solution to reduce dependence on wheat flour. Yellow sweet potato has an energy value similar to wheat fl our, as well as isolated soy protein high in protein and moringa leaves powder high in calcium. The purpose of this research was to analyse the effect of yellow sweetpotato, isolated soy protein, and moringa leaves powder substitution on acceptability and nutritional value (energy, protein, and calcium) of instant noodle. This was experimental research with completely randomized design. There were three formulas, one as a control formula (F0) and two substitution formulas with yellow sweet potato, isolated soy protein, and moringa leaves (F1 and F2) with 8 repetitions. There were 33 pregnant women as untrained panelist. The difference test was analyzed by Kruskall Wallis and Mann Whitney (α≤0.05). The result of panelist acceptability showed that the best formula is F2 (substitution of 6.8% yellow sweet potato, 5.4% isolated soy protein, and 1.4% moringa leaves powder). There was a signifi cant difference between F0 with F2 (p=0.004) and F1 with F2 (p=0.013) on aroma characteristics. The highest protein and calcium content per 100 g of instant noodle was F2, with 14 g and 44.5 mg. The best formula which determinated by the acceptability and nutritional value (energy, protein and calcium) was F2 (substitution of 25 g yellow sweet potato, 20 g isolated soy protein, and 5 g moringa leaves powder), so it can be used as an alternative food for pregnant women.